Electromechanical delay and reactive strength indices of sprint and endurance trained athletes - Clegg, M.; Harrison, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
This study compared reactive strength indices and electromechanical delay in muscle of competitive sprint and endurance athletes. Reactive strength indices were obtained from five sprinters and six endurance athletes who completed drop jumps on a force-sledge apparatus at various drop heights. Electromechanical delay times were also obtained on the ankle plantar flexors while performing a simple heel raise activity. The results indicated that sprinters had significantly higher RSI scores at all drop heights. Sprint athletes also had significantly shorter electromechanical delay times indicating a capacity for generating force more rapidly and the likelihood of stiffer musculotendinous structures.